Determining Investment Decision Making on Cryptocurrency assets in Indonesia: The Role of Covid-19’s Perceived Knowledge - Lim, Michelle Angel; Isnaini Nuzula Agustin (Universitas Pamulang, 2024)
The study aims to investigate the impact of several variables such as gambler's fallacy, herding, risk perception, perceived knowledge of COVID-19, attitude, overconfidence, and financial literacy as moderators on investment decisions on cryptocurrency investors in Indonesia. The research use quantitative method with hypothesis analysis based on primary data gathered from 400 respondents via Google Forms. The collected data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that variables such as gambler's fallacy, risk perception, perceived knowledge of COVID-19, attitude, and overconfidence significantly influence investment decisions among Indonesian investors. Meanwhile, herding behavior shows a positive but insignificant impact on investment decisions. Furthermore, financial literacy does not significantly moderate variable between overconfidence and investors in their investment decision-making process. The study concludes that investor psychology plays a crucial role in investment decisions, which cannot be fully controlled merely through enhancing financial literacy. For future research, expanding the respondent base through both online platforms like Google Forms and offline methods will be crucial to ensure a more comprehensive and representative sample. This approach will help in capturing a wider spectrum of investor perspectives and behaviors within the Indonesian cryptocurrency market. Moreover, researchers are encouraged to enhance the depth of analysis by incorporating additional variables beyond those studied here.